(untitled) (Third Sector Social Economic Review, 2020)
This research on the purpose of examine the relationship between the healthcare workers’ five factor personality traits and fears of failure. Because of this purpose, base on quantitative research method was taken as basis. Relational research type and field research design were used according to the study of variables. Researchdata were collected from 400 hospital staff in a training and research hospital operating in a province by means of a questionnaire. The data has been analyzed by using frequency analysis, factor analysis, correlation analysis, independent sample t test and analysis of variance. Results indicate that a low positive correlation was found between the fear of failure and the emotional balance dimension of the personality. A negative relationship between employees’ openness to experience, consicientiousness and aggrebleness personality traits and the fear of failure to decrease their value, On the other hand, there is a positive relationship between the emotional balance personality trait and the fear of important others losing interest. In addition, depending on the demographic characteristics of the participants, results have been obtained that the personality traits and fears of failure differ.